Analisis Pengaruh Pengeluaran Pemerintah dan Tenaga Kerja terhadap Produk Domestik Regional Bruto di Provinsi Jawa Timur Tahun 2014-2018 - Rofiq, Ainur (OECONOMICUS Journal of Economics, 2020)
This research was conducted to determine the effect of government spending and labor on economic growth in East Java Province in 2014-2015. The results showed that government expenditure, labor had a positive and significant effect on Gross Regional Domestic Product (GRDP). Simultaneously, government and labor expenditures affect the Gross Regional Domestic Product (GRDP)